Heritability of MRI Lesion Volume in CADASIL: Evidence for Genetic Modifiers - Opherk, Christian; Peters, Nils; Holtmannspötter, Markus; Gschwendtner, Andreas; Müller-Myhsok, Bertram; Dichgans, Martin (Stroke (1970), 2006)
Background and Purpose— The phenotypic expressivity shows striking variability among individuals with CADASIL (cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy), a small vessel disease caused by mutations in NOTCH3 . However, little is known about the factors that underlie this variability. We sought to quantify the contribution of modifying genetic effects to individual differences in the volume of cerebral ischemic lesions. Methods— One hundred and fifty-one affected individuals (mean age±SD=45.7±10.4) from 95 unrelated families with CADASIL underwent MRI. The volume of lesions visible on T2-weighted images and the intracranial volume (ICV) were quantified and vascular risk factors were assessed. Because of a skewed distribution, lesion volume measures were square-root transformed. Variance component methods were used to estimate the heritability of lesion volumes (ie, the proportion of variation caused by additive genetic factors) after adjusting for covariates. Results— In multivariate analyses, higher age, a larger ICV, and a higher diastolic blood pressure were independently associated with a larger volume of T2-visible lesions (all P <0.05). After adjustment for age the point estimate for the heritability of the square-root-transformed measure of T2 lesion volume was 0.634 (SE=±0.286). Adjustment for age, sex, ICV, and diastolic blood pressure increased the estimated heritability to 0.738 (SE±0.255). Conclusions— Heritability estimates in CADASIL suggest a strong modifying influence of genetic factors distinct from the causative NOTCH3 mutation on the amount of ischemic brain lesions. These findings justify a systematic search for genetic variants that modify disease progression.